Perspektif Islam Mengenai Pinjaman Online: Cepat Cair, Lambat Sadar, Berat Tanggungan Dunia dan Akhirat - Rifa Hafizhah Rukmana; Yasmin Humaira Azzahra; William Ishaq Juarsyah Gusti N; Muhammad Parhan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to explore alternative online loans that are in accordance with Islamic principles and their relevance to universities, as well as to understand how universities can play an active role in providing more ethical and responsible online loan alternatives for their students. The research method used is literature analysis and case study, by collecting data from various relevant sources and conducting in-depth analysis of the concept of Islamic-based online loans and their implementation in universities. The results show that Islamic-based online loans, zakat funds, infaq and sadaqah, strict regulations, development of Islamic-based online loans, financial education, and cooperation with Islamic financial institutions can be more ethical and responsible financial solutions for students. The discussion of the results shows that universities can play an active role in providing more ethical and responsible online loan alternatives for their students by collaborating with Islamic financial institutions and developing comprehensive financial education programs. This study also shows that awareness of the importance of finance in accordance with religious and ethical values is crucial in creating a generation that is more caring and responsible in managing their finances and lives. Thus, this study can contribute to the development of more effective university policies and programs in supporting student welfare and increasing awareness of the importance of finance in accordance with religious and ethical values.